MODAL SOSIAL PEREMPUAN PELAKU INDUSTRI RUMAHAN EMPING MELINJO - Saleh, Khaerul (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2017)
This study aims to examine the role of social capital in enhancing the capacity of rural women offenders “emping melinjo” home industry in the province of Banten. The research location is divided into three zones, Industry Zone, Agriculture and Tourism Zone, the respondents 453 people. The analysis used in this research is descriptive statistics, and one-way ANOVA. Results obtained by analysis; Social resources in the form of family relationship (kindship family), friendship (relationship conectivity) strengthen the level of confidence (trust), social networking (social networking) liabilities (obligations) and proactive (proactive actions) on social capital micro is a bridge (bonding) capable stir the creativity and ability of rural women. Patterns of cooperation that built in the home industry is a process of social change, such as changes in work patterns and the patterns of living, the goal is the increase in income and family welfare (income generating and family welfare). Micro social capital is still dominated by the behavior of rural women tends partlinear consequently closed, and results in weak level of confidence (distrust), this can be seen from the attitude of individuality is still high. At the meso level of social capital in the form of social networks and relationships.